2010
DOI: 10.1021/jp103223u
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences Between Cyclodextrin−Sodium Dodecyl Sulfate Host−Guest Complexes of Different Stoichiometries: Molecular Dynamics Simulations at Several Temperatures

Abstract: An extensive dynamic and structural characterization of the supramolecular complexes that can be formed by mixing α-, β-, and γ-cyclodextrin (CD) with sodium dodecyl sulfate (SDS) in water at 283, 298, and 323 K was performed by means of computational molecular dynamics simulations. For each CD at the three temperatures, seven different initial conformations were used, generating a total of 63 trajectories. The observed stoichiometries, intermolecular distances, and relative orientation of the individual molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 62 publications
7
68
0
Order By: Relevance
“…The type of molecules that can be introduced in the cavity to form an inclusion complex, depends mainly on geometric factors rather than on chemical properties, however these are evidently not the only factors, it is shown that the ability of CDs to form supramolecular assemblies is also due to the effect of conformational adaptation of the host and the guest molecules. In some cases the CD hardly modifies his atomic positions by the inclusion complex formation [3,4], but there are some compounds capable of changing the truncated cone shaped structure of CDs to nanocylinder-like blocks [5,6]. The present work considers the CD cavity like a conical geometry, to take into account these structural changes it could be applied the characteristics of a continuum model for the interaction energy of a cylindrical structure for CDs studied in previous work [7].…”
Section: Introductionmentioning
confidence: 99%
“…The type of molecules that can be introduced in the cavity to form an inclusion complex, depends mainly on geometric factors rather than on chemical properties, however these are evidently not the only factors, it is shown that the ability of CDs to form supramolecular assemblies is also due to the effect of conformational adaptation of the host and the guest molecules. In some cases the CD hardly modifies his atomic positions by the inclusion complex formation [3,4], but there are some compounds capable of changing the truncated cone shaped structure of CDs to nanocylinder-like blocks [5,6]. The present work considers the CD cavity like a conical geometry, to take into account these structural changes it could be applied the characteristics of a continuum model for the interaction energy of a cylindrical structure for CDs studied in previous work [7].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction energy between -CD and a linear molecule is represented by the van der Waals contribution, modelled by a Lennard-Jones (6,12) potential. It depends on two parameters ( , ), where is the depth of the well and is the position where the repulsive branch crosses zero [22][23][24].…”
Section: Simulation Methodsmentioning
confidence: 99%
“…A well-known experimental finding is the existence of an appropriate size of the guest to reach maximum binding affinity in each CD [4][5][6][7], but there is no theoretical justification for this result and the factors influencing this affinity are not known. CDs and their inclusion complexes have been theoretically studied using different computational methods: molecular mechanics (MM) [8,9], molecular dynamics (MD) [6,10], and Monte Carlo simulations (MC) [11,12], where all the atoms of both CDs and guest molecules have been described.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Some of the 1:2 and 2:1 mol/mol host-guest Abstract: Self-assembled, noncovalent polymeric biodegradable materials mimicking proteoglycan aggregates were synthesized from inclusion complexes of cationic surfactants with g-cyclodextrin and the natural anionic polymer hyaluronan. The amorphous structure of this ternary system was proven by X-ray diffraction and thermal analysis.…”
Section: Introductionmentioning
confidence: 99%